Laser-induced valence electron excitation in acetylene - Hu, Hongtao; Hung, Yi; Larimian, Seyedreza; Erattupuzha, Sonia; Baltuška, Andrius; Zeiler, Markus; Xie, Xinhua (Frontiers in Physics, 2022)
Strong-field induced valence electron excitation is a common process in strong field interaction with atoms and molecules. In the case of polyatomic molecules, the effects of ionization from low-lying molecular orbitals and nuclear dynamics during the interaction can play critical roles for electron excitation. In this work, we investigate the involved molecular orbitals in the electron excitation of singly ionized acetylene in a strong laser field using alignment dependence and laser intensity dependence. Additionally, the involved nuclear dynamics during the electron excitation are identified from the difference in the kinetic energy release and the angular distribution of laser-induced dissociation with different pulse durations and intensities. The laser intensity dependence clearly shows the relative strength change of two excitation pathways in the measured momentum and angle-resolved distributions.